Sustainable Water-Energy-Food Nexus Modeling to Anticipate Land Use Changes in Magelang Regency - Zulfikar Aji Kusworo; Muhammad Sulaiman; Rachmawan Budiarto (Institute for Research and Community Service (LPPM), Universitas Malikussaleh, Indonesia, 2024)
This paper aims to analyze the integrated management of water, energy, and food resources within the context of the Water-Energy-Food (WEF) Nexus in Magelang Regency, Central Java, Indonesia. The focus is on the projections for electricity demand, water needs, and potential electricity production from microhydro power plants (PLTMH) by 2030. The methodology involved simulation models using the LEAP and WEAP software to create a conceptual management model that promotes sustainable resource use. Our findings project electricity needs in Magelang Regency to increase significantly, estimated at 79,626.3 MWh under the baseline business-as-usual scenario, 90,281.53 MWh for a moderate scenario, and 92,201.78 MWh under an optimistic scenario, with the moderate and optimistic scenarios representing increases of 13.38% and 15.79%, respectively, over the baseline by the end of the projection period. Concurrently, water demand is projected at 349,953,115 m³ under the baseline scenario and slightly less at 339,542,991 m³ considering the impact of the new Yogyakarta-Bawen toll road, with a variance of 3.07% between the scenarios by 2030. Additionally, the potential electricity production from the proposed PLTMH is projected at 590.67 MWh by 2030. These projections underscore the critical contributions of sustainable infrastructural developments such as PLTMH, which, despite regulatory support, have not yet been constructed in the regency. This research illustrates the need for robust planning and integration of sustainable practices within local governance to achieve the objectives outlined in the Sustainable Development Goals (SDGs), emphasizing the importance of sustainable and innovative solutions to meet future demand for these interconnected resources effectively.